2015
DOI: 10.2174/1381612822666151112153117
|View full text |Cite
|
Sign up to set email alerts
|

Guggulsterone for Chemoprevention of Cancer

Abstract: Guggulsterone [4, 17(20)-pregnadiene-3, 16-dione] is a plant sterol derived from the gum resin of the tree Commiphora wightii. The gum resin of the guggul tree has been used in traditional medicine for centuries to treat obesity, liver disorders, internal tumors, malignant sores, ulcers, urinary complaints, intestinal worms, leucoderma, sinus, edema and sudden paralytic seizures. Guggulsterone has been shown to modulate the nuclear receptors, farnesoid X receptor, pregnane X receptor, CYP 2b10 gene expression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Thus, a critical evaluation of the binding interaction of ligands with GR was done and suggested that boswellic acid and withaferin A displayed better binding modes with GR compared with the other tested ligands, where withaferin A interacted with two active site amino acids similar to those that fluticasone interacted with and boswellic acid interacted with three active site amino acid residues, which was even better than fluticasone. Previous in silico and/or in vitro studies suggested that these plant steroids might interact with GR, including glycyrrhetinic acid [22], guggulsterone [23], boswellic acid [24], withaferin A [25], and diosgenin [26]. However, none of the previous studies compared more than one plant steroids or referred their effect to a standard GR ligand as fluticasone.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a critical evaluation of the binding interaction of ligands with GR was done and suggested that boswellic acid and withaferin A displayed better binding modes with GR compared with the other tested ligands, where withaferin A interacted with two active site amino acids similar to those that fluticasone interacted with and boswellic acid interacted with three active site amino acid residues, which was even better than fluticasone. Previous in silico and/or in vitro studies suggested that these plant steroids might interact with GR, including glycyrrhetinic acid [22], guggulsterone [23], boswellic acid [24], withaferin A [25], and diosgenin [26]. However, none of the previous studies compared more than one plant steroids or referred their effect to a standard GR ligand as fluticasone.…”
Section: Discussionmentioning
confidence: 99%
“…ex Stocks) Engl.). Guggulsterone is broadly utilized in Indian traditional medicine for the management of various diseases, including cancer [247][248][249]. It suppressed U266 cell proliferation by inducing apoptosis and cell cycle arrest at the sub-G 1 phase.…”
Section: Guggulsteronementioning
confidence: 99%
“…FXR antagonists are numerous and are both natural and synthetic [31]. Guggulsterone is a vegetal sterol derived from the resin of an Asian tree Commiphora wightii and has been consumed in traditional medicine for centuries to treat obesity, liver disorders and a large panel of tumors [45]. This molecule is often used in preclinical in vitro and in vivo studies and showed a decrease of FXR activity and the tumor size [46].…”
Section: Discussionmentioning
confidence: 99%